Entrepreneurship education in the nineties - Mcmullan, W.Ed; Long, Wayne A. (Journal of Business Venturing, 1987)
Bringing entrepreneurship education into the community support infrastructure poses one of the more important economic development issue for the 1990s. Aspart of the new strategy for job creation, entrepreneurship education holds promise as an integral component in a community's venture support system along with incubators, innovation centers, technology transfer offices, science parks, and venture capital operations. Since new venture success is foremost a function of entrepreneurial knowledge and know-how, entrepreneurship education may be the most promising of these economic development mechanisms. Unfortunately, it may be the most difficult to implement. Generally the extent and nature of education required by modern aspiring entrepreneurs is not well understood. Many would see entrepreneurship education as strictly an add-on to current education in management or engineering. Such is the option of minimal use. The real promise or entrepreneurship education will be realized when it is strategically organized for economic development and job creation. This article traces the recent history of entrepreneurship education before proceeding to deal with a number of questions facing those who would use entrepreneurship education as part of a modern economic development strategy:1.1. Why is entrepreneurship education important?2.2. How should it be distinguished from related programs?3.3. How will success be measured?4.4. Who will be the students?5.5. How will the subject be taught?6.6. What will be the curriculum?7.7. Who will be the teachers?